Methodological issues in syntax, under the pretext of 'hand' (Atti del Sodalizio Glottologico Milanese, 2019)
This work examines four Italian constructions which on the surface appear to resemble each other. In all these constructions, the noun mano ‘hand’ apparently functions as a direct object. Conducted from a functional perspective, the research outlined in this paper demonstrates how such constructions differ greatly from each other. Such an analytic result is achieved by virtue of a simple definition of the different values for mano based on the well-known “rapports syntagmatiques et rapports associatifs”. Thus, from a methodological standpoint these pages demonstrate how a realistic and rational approach to syntax obviates the need for the panoply of notions and tools which are currently used by many theoretical frameworks. KEYWORDS: method, syntax, Italian, hand, constructions